Communication from the executive of the Commonwealth, transmitting the credentials of commissioners from South Carolina and Mississippi (LLMC-digital (Series), 1861)
Correspondence between Virginia state governor John Letcher, South Carolina state governor F.W. Pickens, and Mississippi state governor John J. Pettus, and others regarding the 1861 credentials of the South Carolina and Mississippi Commissioners, who were appointed following their respective secession conventions.